(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to determine the impact of social media, with its dimensions (dissemination and use, content, interaction, and influence), on building cultural diversity strategies (arts and cultural traditions) with its dimensions (preservation, promotion, development, and exchange). The study used a descriptive and analytical approach to uncover the resulting effects of social media, with its dimensions (dissemination and use, content, interaction, and influence), on building cultural diversity strategies (arts and cultural traditions) with its dimensions (preservation, promotion, development, and exchange). The study instrument was a questionnaire as the primary tool for collecting data from users of social media platforms and those interested in arts and cultural traditions in Saudi Arabia. The study population consists of all individuals in the Kingdom of Saudi Arabia who use social media and are interested in arts and cultural traditions. A sampling method was adopted to determine an appropriate number of participants who accurately represent the original community. The Krejci and Morgan equation was used, determining the required sample size at 384 individuals. The results demonstrated the impact of social media in its dimensions (dissemination and use, content, interaction, and influence) on the development of cultural diversity strategies (arts and cultural traditions) in its dimensions (preservation, promotion, development, and exchange). The study also recommends the need for mechanisms to improve the quality of cultural diversity according to social and ethical standards. It also recommends conducting future studies, including the role of social media in promoting global cultural diversity in accordance with the Kingdom of Saudi Arabia’s Vision 2030.